Caste System: Theories and Practices in Nepal - Subedi, Madhusudan (Himalayan Journal of Sociology and Anthropology, 2011)
There has been a long debate in the literature over whether the caste system is a unique social phenomenon or simply one manifestation of processes of social stratification which have a wider generality. New divisions and differentiations have been giving rise to new antagonism and social norms. Caste is not today what it was before 1950; and it has not become completely class or replica of it in Nepal. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4672 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 134-159